2019
DOI: 10.1007/s42452-019-0434-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acid pretreatment on the hydrodeoxygenation performance of carbon supported RuMo bimetallic catalysts on sorbitol conversion

Abstract: Sorbitol was reported as one promising platform compounds as a C6 sugar related derivative from biomass cellulose due to its high oxygen content with six hydroxyl groups. Our previous work has reported the selective hydrodeoxyenation (HDO) of sorbitol into long alkanes such as pentane and hexane (C5/C6) over carbon supported ruthenium-molybdenum catalysts. Here, the effect of acidic pretreatments of those carbon catalysts on the performance of HDO reaction was studied in detailed. The result indicated that car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…5 (b), where the spectra of heterogeneous materials exhibited a D band at around 1350 cm -1 and a G band at around 1580 cm -1 , corresponding to the disordered arrangement of graphite lattice structures and the stretching of sp 2 atomic pairs on carbon ring or long carbon-chain in graphite, respectively 36 . The value of La was calculated through the strength of D and G bands as previously reported (Co@C-600-EtOH: 27.5; Co/CoO@C-600-EtOH: 23.0), which confirmed that the oxidation step reduced the graphitization of carbon-supported catalysts 37 . Acid functional groups were detected on the catalyst surface by means of FTIR spectra shown in Fig.…”
Section: Structural and Catalytic Features Of Catalystsupporting
confidence: 68%
“…5 (b), where the spectra of heterogeneous materials exhibited a D band at around 1350 cm -1 and a G band at around 1580 cm -1 , corresponding to the disordered arrangement of graphite lattice structures and the stretching of sp 2 atomic pairs on carbon ring or long carbon-chain in graphite, respectively 36 . The value of La was calculated through the strength of D and G bands as previously reported (Co@C-600-EtOH: 27.5; Co/CoO@C-600-EtOH: 23.0), which confirmed that the oxidation step reduced the graphitization of carbon-supported catalysts 37 . Acid functional groups were detected on the catalyst surface by means of FTIR spectra shown in Fig.…”
Section: Structural and Catalytic Features Of Catalystsupporting
confidence: 68%
“…Introduction of phosphorus‐containing functional groups are studied to regulate catalytic performance through acidity, hydrophilicity, chemical state of metal active phase of catalyst [13] . Phosphorus‐group introduced through H 3 PO 4 on AC surface is beneficial to provide enough Brønsted acid sites (>95 %) and significant acid strength to activate oxy‐groups, reduce coke formation and keep good stability at high temperature [78,61b] .…”
Section: Surface Functionalization Of Carbon Materialsmentioning
confidence: 99%
“…The noble metals (Rh, Pt, Pd), base metals (Fe, Ni), alloys (Fe/Pd alloys), and compounds (nickel phosphide, molybdenum carbide) are usually used as metal active phases to drive HDO reactions [11–12] . Metal active phases on support can lead to different degrees of hydrogenation of C=O and C=C bonds and side reactions, such as hydrogenolysis or cleavage of C−C bonds, isomerization, and hydration [13] . Therefore, the formation, dispersion, and distribution of active metal nanoparticles (NPs) on support surface are the key factors affecting activity of catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loading a noble metal to a carrier, such as loading Ru to TiO 2 , ZrO 2 , and carbon [13,14] and loading Au to Al 2 O 3 , SiO 2 , and TiO 2 [15,16], can increase the metal particle dispersity, prevent the carbon deposition and favor the contact of reactant with the active site, and further increase the stability and catalytic activity of catalyst. However, noble metal particle catalysts are expensive and suffer from low utilization and difficulty in recycling.…”
Section: Introductionmentioning
confidence: 99%